Phytomediated selenium nanoparticles and light regimes elicited in vitro callus cultures for biomass accumulation and secondary metabolite production in Caralluma tuberculata - Ali, Amir; Mashwani, Zia-ur-Rehman; Raja, Naveed Iqbal; Mohammad, Sher; Luna-Arias, Juan Pedro; Ahmad, Ajaz; Kaushik, Prashant (Frontiers in Plant Science, 2023)
Caralluma tuberculata holds significant importance as a medicinal plant due to its abundance of bioactive metabolites, which offer a wide range of therapeutic potentials. However, the sustainable production of this plant is challenged by overexploitation, changes in natural conditions, slow growth rate, and inadequate biosynthesis of bioactive compounds in wild populations. Therefore, the current study was conducted to establish an in vitro based elicitation strategy (nano elicitors and light regimes) for the enhancement of biomass and production of secondary metabolites. Garlic clove extract was employed as a stabilizing, reducing, or capping agent in the green formulation of Selenium nanoparticles (SeNPs) and various physicochemical characterization analyses such as UV visible spectroscopy, scanning electron microscopy (SEM), energy dispersive X-Ray (EDX) Spectroscopy, fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) were performed. Furthermore, the effects of phytosynthesized SeNPs at various concentrations (0, 50, 100, 200, and 400 µg/L) on callus proliferation and biosynthesis of medicinal metabolites under different light regimes were investigated. Cultures grown on Murashige and Skoog (MS) media containing SeNPs (100 µg/L), in a dark environment for two weeks, and then transferred into normal light, accumulated maximum fresh weight (4,750 mg/L FW), phenolic contents (TPC: 3.91 mg/g DW), flavonoid content (TFC: 2.04 mg/g DW) and 2,2-Diphenyl-1-picrylhydrazyl (DPPH) antioxidant activity (85%).Maximum superoxide dismutase (SOD: 4.36 U/mg) and peroxide dismutase activity (POD: 3.85 U/mg) were determined in those cultures exposed to SeNPs (100 µg/L) under complete dark conditions. While the callus cultures proliferate on media augmented with SeNPs (200 µg/L) and kept under dark conditions for two weeks and then shifted to normal light conditions exhibited the highest catalase (CAT: 3.25 U/mg) and ascorbate peroxidase (APx:1.93 U/mg) activities. Furthermore, LC-ESI-MS/MS analysis confirmed the effects of SeNPs and light conditions that elicited the antidiabetic metabolites (cumarins, gallic acid, caffeic acid, ferulic acid, catechin, querctin and rutin). This protocol can be scaled up for the industrial production of plant biomass and pharmacologically potent metabolites using in vitro callus cultures of C. tuberculata.